2015
DOI: 10.1016/j.jagp.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Clinical Diagnosis and Medicare Claims of Depression Among Older Primary Care Patients

Abstract: Objective To identify patient characteristics associated with concordance of Medicare claims with clinically identified depression. Design Cohort of 742 older primary care patients linked to Medicare claims data. Measurements Structured Clinical Interview for DSM-IV major depressive disorder (MDD) and clinically-significant minor depression. Results Among 474 patients with depression, 198 patients had a Medicare claim for depression (sensitivity: 42%, 95% confidence interval (CI) 37% to 46%). Among 268 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…15 A Canadian study in 2002 found no difference between depressed and non-depressed in enrollment in CR but did find that those with anxiety were 1.9 (CI: 1.0, 3.4) times more likely to enroll in CR compared to those without anxiety. 27 A more recent study of CR programs enrolled in the Wisconsin Cardiac Rehabilitation Outcomes Registry (WiCORE) observed that patients with depression were 44% less likely to enroll in CR compared to those without depression. 16 Patients in the study were those referred to CR and may be different than those not referred.…”
Section: Discussionmentioning
confidence: 99%
“…15 A Canadian study in 2002 found no difference between depressed and non-depressed in enrollment in CR but did find that those with anxiety were 1.9 (CI: 1.0, 3.4) times more likely to enroll in CR compared to those without anxiety. 27 A more recent study of CR programs enrolled in the Wisconsin Cardiac Rehabilitation Outcomes Registry (WiCORE) observed that patients with depression were 44% less likely to enroll in CR compared to those without depression. 16 Patients in the study were those referred to CR and may be different than those not referred.…”
Section: Discussionmentioning
confidence: 99%
“…Some negative values can be found (especially in clusters 1 and 2), suggesting patients wrongly classified, but even those clusters have a fairly decent index. Cluster 1 (Chronic diseases, n = 1463) is a medium-sized cluster that has been built around a number of diagnoses previously associated with depression: endocrine diseases [26,27] and the circulatory [28][29][30][31], respiratory [6,29] and genitourinary systems [32]. Of all the clusters obtained, this is the one that includes the highest number of diagnoses with a prevalence greater than 25%, although none (with the exception of F32) is present in more than 66.2% of the patients.…”
Section: Cluster Analysismentioning
confidence: 99%
“…The fact that the Medicare Claims measure identified 12% of the sample as depressed and the PHQ-2 measure only identified 7% of the sample as depressed may indicate that the Medicare Claims variable is the more sensitive measure, although this is contradictory to studies examining the sensitivity and specificity of Medicare Claims (Hwang et al, 2015;Noyes et al, 2011). The PHQ-2 is less sensitive to types of depression other than major depression (Arroll et al, 2010).…”
Section: Sample and Methodological Issuesmentioning
confidence: 91%
“…This measure had a sensitivity of 42% and a specificity of 88%. when compared to SCID interviews to identify major and minor depression (Hwang et al, 2015). Hwang and colleagues also Claim depression data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation